2015
DOI: 10.1261/rna.049148.114
|View full text |Cite
|
Sign up to set email alerts
|

Global miRNA expression and correlation with mRNA levels in primary human bone cells

Abstract: MicroRNAs (miRNAs) are important post-transcriptional regulators that have recently introduced an additional level of intricacy to our understanding of gene regulation. The aim of this study was to investigate miRNA-mRNA interactions that may be relevant for bone metabolism by assessing correlations and interindividual variability in miRNA levels as well as global correlations between miRNA and mRNA levels in a large cohort of primary human osteoblasts (HOBs) obtained during orthopedic surgery in otherwise hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…This finding is in contradiction to the generally expected repressive effect of miRNAs on target expression. Nevertheless, positive correlations have also been described in earlier studies on miRNA gene interactions, and thus the function of miRNAs may not be only repressive 21 . Since miRNAs are interwoven into complex regulatory networks, a suppression of a signaling mediator can lead to the transcription of a target gene, and consequently, result in a positive correlation 22 .…”
Section: Discussionmentioning
confidence: 65%
“…This finding is in contradiction to the generally expected repressive effect of miRNAs on target expression. Nevertheless, positive correlations have also been described in earlier studies on miRNA gene interactions, and thus the function of miRNAs may not be only repressive 21 . Since miRNAs are interwoven into complex regulatory networks, a suppression of a signaling mediator can lead to the transcription of a target gene, and consequently, result in a positive correlation 22 .…”
Section: Discussionmentioning
confidence: 65%
“…Altered patterns of miRNA expression have been shown in bone-related pathologies, which may jeopardize progenitor cell commitment and osteogenic differentiation. miR-29b is known to have an important regulatory role in osteoblast differentiation, as it targets cOL1A1 and SPARc (osteonectin) mRNAs (51). As osteoblasts mature, miR-29b attenuates the expression of collagen genes, allowing the organization of collagen fibrils for subsequent mineralization.…”
Section: Role Of Mirnas In the Pathological Osteogenic Commitment Of mentioning
confidence: 99%
“…When certain genes require increased transcription during periods of cellular stress, their repressor miRNAs are downregulated, and vice versa. Yet, studies have shown that as a miRNA is upregulated, its target mRNAs may also show transcription increase, highlighting the complexity of miRNA‐mRNA regulatory dynamics (Laxman et al, ; Nunez‐Iglesias, Liu, Morgan, Finch, & Zhou, ; Vasudevan, Tong, & Steitz, ). Such counter‐intuitive positive correlations may be the result of downstream feedbacks (Martinez, Ow, & Barrasa, ).…”
Section: Discussionmentioning
confidence: 99%